If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + ln(27x) = 24 + -2ln(x) Remove parenthesis around (27x) 3 + ln * 27x = 24 + -2ln(x) Reorder the terms for easier multiplication: 3 + 27ln * x = 24 + -2ln(x) Multiply ln * x 3 + 27lnx = 24 + -2ln(x) Multiply ln * x 3 + 27lnx = 24 + -2lnx Solving 3 + 27lnx = 24 + -2lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '2lnx' to each side of the equation. 3 + 27lnx + 2lnx = 24 + -2lnx + 2lnx Combine like terms: 27lnx + 2lnx = 29lnx 3 + 29lnx = 24 + -2lnx + 2lnx Combine like terms: -2lnx + 2lnx = 0 3 + 29lnx = 24 + 0 3 + 29lnx = 24 Add '-3' to each side of the equation. 3 + -3 + 29lnx = 24 + -3 Combine like terms: 3 + -3 = 0 0 + 29lnx = 24 + -3 29lnx = 24 + -3 Combine like terms: 24 + -3 = 21 29lnx = 21 Divide each side by '29nx'. l = 0.724137931n-1x-1 Simplifying l = 0.724137931n-1x-1
| 21x^4+60x^3y-9x^2y^2= | | 3y-1=5y-11 | | 9z-2=25 | | 5x^2-20x-20=5 | | 2b-6+36=-8 | | 1/3x+1/2x+1/3=9/2 | | w/3-10=-60 | | 32x-14=178 | | 10+7x=-46 | | 4x^2-40x+40= | | -4+5/3n=16 | | 18a-13+2a=6a+23 | | 2x+7/3=x-1/4 | | 3x^2-24x+144=149 | | 4p-3=-23 | | 26/13 | | (x^2D^2-4xD-6I)y=0 | | x+2x+6=12 | | 3y+1=4y+4 | | 200x=2500 | | 5x^2-50x+75= | | 5x-10=-7x+14 | | 8x+6=-40 | | 4a^2-19a-30=0 | | 15x^2+67x+72=0 | | 100x^2+10x+1=0 | | 40x-x^2=50 | | x^4+2x^3-24x^2=0 | | x^5+2x^3-24x^2=0 | | 3/4a+5=7/3 | | 6h+7k-9(3h-6k)= | | 5x+5+7x-15=2 |